P5 Proyek Bukan Produk - Hafriani, Masri, Sarah fazila (JKA, 2024)
The P5 Program, or Pancasila student profile Strengthening Project, and the PPRA program, or Rahmatan Lil Alamin student profile, are new innovations in the education curriculum that aim to improve the character and abilities of students as a whole. P5 centers on six dimensions: faith, global diversity, mutual aid, self-reliance, critical thinking, and creativity. Instead, the PPRA emphasizes moderate religious principles such as justice, tolerance, civility, and citizenship. Both of these programs aim to cultivate students ' personalities as Indonesian citizens and people around the world. The method of implementation of these two programs involves international PKM activities with the theme "the Role of Academia and Headmaster to Enhance Overall Educational Quality in the Digital Era."This activity involves collaboration with 33 campuses in Indonesia, Universiti Utara Malaya, Monash University Australia, the Ministry of Religious Affairs of Central Aceh Regency, and the branch of the Regional Education Office of Central Aceh Regency. The stages of activities include licensing, socialization, implementation, and evaluation. The delivery of the material "P5 is not a product" to the principals of various educational institutions is one of the results of international PKM activities. In addition to providing guidance to principals, this presentation aims to build students ' character through values such as character education, example, tolerance, and communication. To ensure the achievement of the objectives of the PKM, the positive impact on society, and the sustainability of activities after the PKM ends, a thorough evaluation is carried out.